Ojibwe materials, American Philosophical Society Historical and Literary Committee, American Indian Vocabulary Collection - Heckewelder, John Gottlieb Ernestus, 1743-1823 (1820)
The Chippewa or Ojibwe materials in this collection consist of manuscript Vocabularies listed in the finding aid as items 20, 21, 22a, and 22b.